Hattie's "Visible Learning" in Islamic religious education. What works to what effect? - Topalovic, Said (Österreichisches Religionspädagogisches Forum, 2019)
The study Visible Learning published by John Hattie, Professor of Education from New Zealand, is celebrating its anniversary. The first publication dates back ten years. Hattie's study enriched numerous debates surrounding school teaching, new aspects were taken up, old discussions revived. It is against this backdrop that the present article seeks to discuss selected performance indicators of students and their relevance for Islamic religious education: what works to what effect and how can this, in turn, contribute to improving the quality of Islamic religious education?
CRIS-Team WoS Importer:2019-06-07